Prawda cytatu, czyli o grze alegacjami (na podstawie cyklu „Paryskie pasaże" Krzysztofa Rutkowskiego) - Szalewska, Katarzyna (Przestrzenie Teorii, 2008)
The aim of this article is to consider the relationship between the practice of quoting and truth on the example of Krzysztof Rutkowski's oeuvre. In an obvious way such an interpretation of the subject brings reflections closer to the analyses of intertextuality, however, that which distinguishes intertextual references in the texts discussed from the postmodernistic play with conventions is a different function of the hypotext present through quotations. First of all, it has to validate, i.e. also to axiologically mark the essayist's exposition. The practice of quoting reminds an act of allegation, however, with the reservation that it allows the element of the dialogue. Thus, this article is both an attempt at an analysis of the ways of functioning in the composition of an essay of attempts at imitation as textual strategies as well as - and mostly - combination of the allegation game with the problem of literary truth, the truth of the subject of the essay, but also of the truth expected in the reception by the readers.